Development of a geometrical model for the determination of the average intensity in a flow-through UV-LED reactor and validation with biodosimetry and actinometry. (October 2022) - Romero-Martínez, Leonardo; Moreno-Andrés, Javier; Acevedo-Merino, Asunción; Nebot, Enrique
Abstract: Ultraviolet (UV) treatment is widely used for water disinfection. The recent development and improvement of the light emitting diodes (LEDs) in the UVC range makes them an alternative to the traditional mercury vapor UV lamps in the middle or long term. Determining the UV intensity applied by a reactor is essential for evaluating its efficacy. Although doing so is relatively straightforward in simple laboratory reactors, such as a collimated beam reactor (CBR), its calculation for more complex devices, such as a flow-through reactor (FTR), requires indirect approaches. The objective in this study is determining the UV intensity in FTRs equipped with UV-C LEDs by utilizing indirect approaches such as the geometrical modeling of the intensity distribution, chemical actinometry, and biodosimetry using a CBR as a reference. With this method, the inactivation of four bacterial indicators in both the CBR and FTR have also been addressed. The three approaches that were used reported similar values of mean intensity with an average value of 0.86 mW cm −2 . Determining the mean intensity enabled calculating the UV doses that were applied to the target water and then determining the inactivation kinetics parameters. The UV dose that was necessary to achieve four-log reductions from the initial bacterial concentration ranged from 5.8 to 17.5 mJ cm −2 depending on the target species. Additionally, the geometrical model developed in this study introduces new possibilities into the optimization of the reactor design. Graphical abstract: Unlabelled Image Highlights: We have developed a light distribution model for a flow-through LED-UV reactor. The model allows calculating the mean intensity and thus the UV dose applied. We have validated the model with chemical actinometry and biodosimetry. The bacteria E. coli and V. alginolyticus showed better time-intensity reciprocity. UV dose of 17.5 mJ cm −2 reached 4-log reductions of the most resistant organism.